REVAMPING AND SIMULATION OF FURFURAL PRODUCTION WHIT ETHANOL TECHNOLOGY OF BAGASSE - Verelst, Harry; Morales Zamora, Marlén; Mesa Garriga, Leyanis; González Suárez, Erenio (Centro Azúcar Journal, 2010)
The integral use of sugar cane, evaluation of alternatives for intensification and revamping of industrial facilities is necessary for the competitive development of this industry. Bagasse is a by-product used for cogeneration and furfural production, boards and ethanol of lignocellullosic residuals. The furfural hydrolysis stage coincides with the first acid stage of pretreatment of ethanol technology of lignocellullosic residuals. From the best obtained results in the ethanol technology of lignocellullosic residuals1 and changing the operation conditions of furfural hydrolysis, with smaller reaction time2 obtained a usable residual and condensed of furfural with an appropriate composition. The work has as objective to carry out simulation of furfural production process for revamping whit ethanol technology of lignocellullosics residuals using the software ASPEN PLUS 11.1. The balances of mass and energy are determined in the acid hydrolysis stages of the bagasse and furfural distillation. Different economic alternatives technical from production from the results of the simulation are analyzed. It is obtained that possibilities of reanimation a furfural plant exist for revamping with the ethanol technology of lignocellullosic residuals. For them it is necessary to take advantage and to adapt the capacities installed to the new technological conditions from the equipment in the plant and to adapt the power availability of raw materials and carriers in the sugar complex.